"These aren't the SLOC's you're looking for": mirror-imaging battles of the Atlantic won't solve current Atlantic security needs. Issue 1 (2nd January 2020) - Wills, Steve
ABSTRACT: Discussion surrounding the announcement of a new NATO Maritime Command for the North Atlantic seems to have settled on the assumption that there is again a vital "sea-line of communication" (SLOC) between North America and Europe as there was supposed to be during the Cold War. The Soviet Union had a large fleet of nuclear and conventional submarines and it seemed very clear that Soviet admirals intended to fight a third "Battle of the Atlantic" in the event of war to prevent Western resupply of NATO. However, this scenario bore no resemblance to what the Soviet Navy actually intended to do in case of war. Changes in technology, notably in submarine propulsion, antisubmarine warfare (ASW), and ballistic missile range and accuracy were the real drivers of the Cold War in the Atlantic. Cruise missile-armed submarines that can attack shore-based economic infrastructure are the real threat from the Russian submarine force.